The Asian Coalition for Community Action's Approach to Slum Upgrading - World Bank Group (Washington, DC, 2014)
This paper is a review of the experience of the Asian Coalition for Community Action (ACCA) Program operated by the Asian Coalition for Housing Rights (ACHR). The objective is to examine what ACCA has accomplished in three years of operation (2009-2012) under a Gates Foundation grant. The review is based on field visits to three of the countries served by ACCA Thailand, Cambodia, and Vietnam and discussions with community leaders from three other countries Nepal, the Philippines, and Sri Lanka. Numerous discussions were held with the ACHR leadership, staff from the Community Organization Development Institute (CODI) of Thailand, and the Thailand Development Research Institute (TDRI).1 In addition, a review was conducted of the literature prepared by and about ACHR, as well as a filtering and synthesis of the status of the cities and countries that made use of ACCA in terms of their broader economic conditions and local governance capabilities. Given that ACCA operates in more than 150 cities in 19 countries, this review is by no means an audited account of its activities.